Lentiviral gene therapy for X-linked chronic granulomatous disease - Kohn, Donald B. (Nat Med, 2020)
Chronic granulomatous disease (CGD) is a rare inherited disorder of phagocytic cells(1,2). We report initial results of nine severely affected X-linked CGD (X-CGD) patients who received ex vivo autologous CD34+ hematopoietic stem and progenitor cell-based lentiviral gene therapy following myeloablative conditioning in first-in-man studies (Trial registry numbers: NCT02234934, NCT01855685). Primary objectives were to assess safety and evaluate efficacy and stability of biochemical and functional reconstitution in the progeny of engrafted cells at 12 months. The secondary objectives included the evaluation of augmented immunity against bacterial and fungal infection, and assessment of hematopoietic stem cell transduction and engraftment. Two enrolled patients died within 3 months of treatment from pre-existing comorbidities. At 12 months, six of the seven surviving patients demonstrated stable vector copy number (0.4–1.8 copies/neutrophil) and persistence of 16–46% oxidase-positive neutrophils. There was no molecular evidence of clonal dysregulation or of transgene silencing. Surviving patients have had no new CGD-related infections, and six have been able to discontinue CGD-related antibiotic prophylaxis. The primary objective was met in 6 of the 9 patients at 12 months follow-up suggesting that autologous gene therapy is a promising approach for CGD patients.